Invasive group B Streptococcus strains and clinical characteristics in Danish infants from 1999 to 2009 - Andersen, Mads; Smith, Birgitte; Murra, May; Nielsen, Stine Yde; Slotved, Hans-Christian; Henriksen, Tine Brink (Frontiers in Microbiology, 2022)
Background Surveillance of Group B Streptococcus (GBS) strains in infants and their clinical characteristics may guide development of effective vaccines and other potential treatments and may have implications for future prognostics and infant care. Therefore, we aimed to study GBS serotypes and clonal complexes in Danish infants with early-onset infection (EOGBS) (0-6 days of life) and late-onset infection (LOGBS) (7-89 days of life) and to estimate the association between GBS strain and different clinical outcomes. Methods We included Danish infants less than three months of age with GBS isolates from blood or cerebrospinal fluid between 1999 to 2009. Samples were sent from the Danish Departments of Clinical Microbiology to the State Serum Institute for analyses. GBS isolates were analyzed by serotyping and multilocus sequence typing with classification of isolates into clonal complexes (CC). Clinical characteristics were obtained by questionnaires completed by tending pediatrician including gestational age, Apgar scores, age at onset, meningitis, symptom severity, treatment duration, and mortality. Symptom severities were reported within neurological symptoms, need for respiratory or circulatory support, and treatment of disseminated intravascular coagulation. Results A total of 212 GBS isolates were collected with 129 from EOGBS and 83 from LOGBS. The dominating GBS strains were III/CC17 (41%), Ia/CC23 (17%), III/CC19 (15%), Ib/CC8-10 (7%), and V/CC1 (6%). Strain Ia/CC23 was mostly found in EOGBS, while III/CC17 was widespread in LOGBS, though being the most common in both EOGBS and LOGBS. Strain III/CC17 and Ia/CC23 had highest percentage of samples from cerebrospinal fluid (26%), while III/CC19 had the least (8%). Strain III/CC19 had highest mortality with about one fifth of infected infants dying (22%) followed by Ia/CC23 (16%), Ib/CC8-10 (9%), and then III/CC17 (6%). The symptom severity varied between strains, but with no strain consistently resulting in more severe symptoms. Conclusion Strain III/CC17 was the most common GBS strain in Danish infants followed by Ia/CC23, III/CC19, Ib/CC8-10, and V/CC1 with Ia/CC23 being associated with EOGBS and III/CC17 with LOGBS. Some potential differences in other clinical outcomes were observed between the strains. These findings emphasize the continuous need for multimodal surveillance of infant GBS strains and their clinical characteristics.